Cortical microstructural changes along the Alzheimer's disease continuum. Issue 3 (25th October 2017) - Montal, Victor; Vilaplana, Eduard; Alcolea, Daniel; Pegueroles, Jordi; Pasternak, Ofer; González‐Ortiz, Sofia; Clarimón, Jordi; Carmona‐Iragui, María; Illán‐Gala, Ignacio; Morenas‐Rodríguez, Estrella; Ribosa‐Nogué, Roser; Sala, Isabel; et al.
Abstract: Introduction: Cortical mean diffusivity (MD) and free water fraction (FW) changes are proposed biomarkers for Alzheimer's disease (AD). Methods: We included healthy control subjects (N = 254), mild cognitive impairment (N = 41), and AD dementia (N = 31) patients. Participants underwent a lumbar puncture and a 3 T magnetic resonance imaging. Healthy control subjects were classified following National Institute on Aging‐Alzheimer's Association stages (stage 0, N = 220; stage 1, N = 25; and stage 2/3, N = 9). We assessed the cortical MD, cortical FW, and cortical thickness (CTh) changes along the AD continuum. Results: Microstructural and macrostructural changes show a biphasic trajectory. Stage 1 subjects showed increased CTh and decreased MD and FW with respect the stage 0 subjects. Stage 2/3 subjects showed decreased CTh and increased cortical MD and FW, changes that were more widespread in symptomatic stages. Discussion: These results support a biphasic model of changes in AD, which could affect the selection of patients for clinical trials and the use of magnetic resonance imaging as a surrogate marker of disease modification.